Gender-Sensitive Materials and Tools: The Development of a Gender-Sensitive Toolbox Through National Stakeholder Consultations - Christou, Eirini; Parmaxi, Antigoni; Perifanou, Maria; Economides, Anastasios A. (My University, 2022)
The values of gender equality are being promoted worldwide. The importance of gender equality for sustainable development is well highlighted by the United Nations Sustainable Goal 5 which notes that the need to end all discrimination against women and girls. Nowadays, most modern scholars argue that the world has made great progress towards gender balance, however, it is far from perfect. For encouraging and empowering women to remain active in every field, it is important to raise awareness about their rights, with emphasis on the vital role of girls and women in the workforce. This is especially important for the Science, Technology, Engineering and Mathematics (STEM) field where women are still underrepresented. This study aims to report on the materials and tools (digital and traditional) that can be used for sensitizing and raising awareness on issues related to gender-equality and women’s empowerment. On this endeavor, we collected information on existing materials used in different contexts through national consultations in Greece, Cyprus, Italy, Spain and Slovenia. The tools and materials collected uncover the various levels of gender equality material available - digital and traditional - taking into account the various facets of gender-equality and provide a comprehensive view to the wider academic and industrial community. This study is expected to provide structured knowledge on a new and rapidly developing topic and add more information to existing contour of knowledge regarding available gender-sensitive materials and tools.
Keywords: Gender-sensitive materials; Gender-sensitive tools